Pemetaan Potensi Objek Wisata Berbasis Sistem Informasi Geografis (SIG) Di Kawasan Catur Desa Adat Dalem Tamblingan Kabupaten Buleleng, Provinsi Bali - Made Sinta Devi Dian Prativa; Atmaja, Dewa Made; Budiarta, I Gede (Universitas Pendidikan Ganesha, 2024)
The objects of tourist attraction owned by Chess Desa Adat Dalem Tamblingan are natural attractions and spiritual tourism. However, these attractions have not maximised the data collection of tourism objects and there is no map of tourism objects so that this research is important to analyse the potential level of tourism objects and map where the distribution of tourism objects in the Chess area of Dalem Tamblingan Traditional Village. This study uses a survey method by applying interview, observation, and documentation techniques for data collection. Analysis was carried out using quantitative descriptive analysis techniques by utilising data from observations and interviews, and correlated using scoring techniques. After calculating each criterion score on each parameter measured, the results are in the form of a map of the distribution of the potential level of tourist attractions in the Traditional Village Chess Area of Dalem Tamblingan. In this Chess Village tourist attraction there are 10 points of tourist attraction distribution locations, of which there are 8 points of great potential, 1 point of potential and 1 point of no potential.